"Violence is just an expression of love and spontaneity": young men's processes of resistance to change after a dating violence prevention program in Turkey - Ustunel, Anil Ozge (Journal of family violence, 2025)
Purpose: Research on gender-based violence prevention programs documents evidence of resistance to committing to non-violence and equality, particularly among some boys and young men. Although a deeper understanding of this resistance is essential to design effective programs, the nature of these reactions still remain largely unexplored in the field of dating violence (DV) prevention. The present study addresses this gap by investigating how a small group of college men manifest resistance to change after completing an eight-week long, feminist-informed DV prevention program in Turkey, and it explores the meaning-making perspectives and discourses that underlie and reinforce this resistance. Methods: Data were collected through semi-structured individual interviews following the program and analyzed with constructivist grounded theory. Out of 56 college students who voluntarily attended the program, the accounts of ten young men demonstrated an overwhelming pattern of resistance and were selected for the present analysis. Results: Their accounts revealed three processes: reframing violence in a positive light, thinking in binaries, and minimizing personal engagement and reflection. These processes drew upon idealized notions of romantic love and spontaneous emotionality, and worked to sustain a sense of masculine entitlement and privilege in the relational domain. Conclusions: The findings indicate that resistance is to be expected as young men become engaged with DV prevention efforts in Turkey and similar patriarchal contexts where tensions around traditional masculinities and egalitarian norms exist. Practice implications for averting and managing young men’s resistance in these efforts are discussed.